Fishbone perforation of the small bowel mimicking internal herniation and obstruction in a patient with previous gastric bypass surgery. Issue 9 (24th September 2020) - Traynor, Paul; Stupalkowska, Weronika; Mohamed, Tahira; Godfrey, Edmund; Bennett, John M H; Gourgiotis, Stavros
Abstract: Intestinal perforation following the ingestion of fishbone is unusual and rarely diagnosed preoperatively, as clinical and radiological findings are non-specific. We report a case of a female patient post Roux-en-Y gastric bypass (RYGBP) for obesity, who presented with severe abdominal pain and guarding in left iliac fossa. Computed tomography (CT) suggested internal herniation with compromised vascular supply to the bowel. Exploratory laparotomy identified a perforation site in the blind loop of the RYGBP due to a protruding fishbone. After extraction, primary suture repair was performed. In retrospect, the fishbone was identified on CT but misinterpreted as suture line at the enteroenterostomy site. This case emphasizes that although rare, the ingestion of fishbone can lead to severe complications and should therefore be included in the differential for an acute abdomen. On CT, it should be noted that fishbone may simulate suture line within the bowel if the patient has history of previous surgery.